The The Effectiveness of Different Sterilant Combination on Citrullus lanatus L. In Vitro: Uji Efektivitas Kombinasi Bahan Sterilan yang Berbeda pada Citrullus lanatus L. secara In Vitro - Indah Lestari, Laras; Irmawati; Negara, Zaidan P.; Hasmeda, Mery; Sulaiman, Firdaus; Sulistyaningsih, Lidwina N.; Marlina (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2025)
Watermelon plants require consistent environmental conditions throughout their growth period. Tissue culture serves as a solution in plant propagation techniques that can control the environmental conditions for watermelon growth. This study aims to determine the appropriate sterilization method and explant type for watermelon plant propagation using tissue culture techniques. The research was conducted from June to August 2022 at the Tissue Culture Laboratory of the Faculty of Agriculture, Sriwijaya University. This study used a Complete Randomized Factorial Design (CRFD) with two factors: six treatments of different sterilization agent sequences for explants, including Benomyl 0.2% for 3 minutes, detergent for 3 minutes, HgCl₂ 0.03% for 10 minutes, and 70% alcohol for 45 seconds, and four types of explants: radicle, hypocotyl, plumule, and cotyledon, with two replicates of five experimental units each. The results showed that sterilization factors and explant types had a significant effect on the percentage of contaminated explants and indicated a decrease in contamination in the treatment of 0.2% benomyl for 3 minutes, detergent for 3 minutes, 0.03% HgCl2 for 10 minutes, and 70% alcohol for 45 seconds on cotyledon explants. Keywords: browning, contamination, tissue culture, watermelon sprout